In vitro pharmacology of fentanyl analogs at the human mu opioid receptor and their spectroscopic analysis - Hassanien, Sherif H. (Drug Test Anal, 2020)
Opioids are widely misused and account for almost half of overdose deaths in the United States. The cost in terms of lives, health care, and lost productivity is significant and has been declared a national crisis. Fentanyl is a highly potent mu opioid receptor (MOR) agonist and plays a significant role in the current opioid epidemic; fentanyl and its analogs (fentalogs) are increasingly becoming one of the biggest dangers in the opioid crisis. The availability of fentalogs in the illicit market is thought to play a significant role in the recent increase in opioid-related deaths. Although there is both rodent homolog in vivo and in vitro data for some fentalogs, prior to this publication very little was known about the pharmacology of many of these illicit compounds at the human MOR (hMOR). Using gas chromatography–mass spectrometry, nuclear magnetic resonance spectroscopy, and in vitro assays, this study describes the spectral and pharmacological properties of 34 fentalogs. The reported spectra and chemical data will allow for easy identification of novel fentalogs in unknown or mixed samples. Taken together these data are useful for law enforcement and clinical workers as they will aid in the identification of fentalogs in unknown samples and can potentially be used to predict physiological effects after exposure.